Deixis Found In Song Lyrics “Divinely Uninspired To A Hellish Extent” Album - Putu Devi Maharani; Komang Dian Puspita Candra; Yanti, Ni Wayan Wahyudi Yanti (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
This study used qualitative method in analyzing the data and documentation method used in collecting the data that found in song lyrics. The data were taken from the song lyrics in Divinely Uninspired to a Hellish Extent album. Based on Cruse (2000) and Cruse (2006) theory there are 507 deixis that found in this study. This study found 369 of person deixis with percentage 73%, 82 data of temporal deixis with percentage 17%, 38 data of spatial deixis with percentage 7%, 7 data of social deixis with percentage 1 % and 11 data of discourse deixis with percentage 2%.